Q. 445.0( 1 Vote )

Mark the correct

Answer :

Given that f(x) = sin–1 x, g(x) = [x2] and

a. goh(x) = g(2x)

goh(x) = [4x2]

fogoh(x) = f([4x2])

fogoh(x) = sin–1 [4x2]

Hence, given option is incorrect.

b. Similarly, this option is also incorrect.

c. fog(x) = f([x2])

fog(x) = sin–1 [x2]

hofog(x) = h(sin–1 [x2])

hofog(x) = 2(sin–1 [x2])

gof(x) = g(sin–1 x)

gof(x) = [(sin–1 x)2]

hogof(x) = h([(sin–1 x)2])

hogof(x) = 2[(sin–1 x)2]

Hence, hogof(x) ≠ hofog(x)

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses

Fill in theMathematics - Exemplar

Let f : [2, ∞) <sMathematics - Exemplar

Let f : N Mathematics - Exemplar

Fill in theMathematics - Exemplar

Let f :R →<Mathematics - Exemplar

Let f : [0, 1] <sMathematics - Exemplar

Which of the follMathematics - Exemplar